Sustainability needs and practices assessment in the building industry of China - Yang, Pingjian; He, Gang; Mao, Guozhu; Yong Liu; Xu, Mingzhu; Guo, Huaicheng; Xi Liu (ENERGY POLICY, 2013)
The building industry in China has huge potential capacity for energy/resources conservation and pollutants reduction to achieve sustainable development However, stakeholders are hardly able to reach a consensus on preferential needs and effective solutions, which was a difficulty faced by policy makers. To better identify the common interests on sustainable development in this field, the Sustainability Solutions Navigator (SSN) was adopted in China for the first time to assess the sustainability needs and practices. Based on the participation of stakeholders from the government, businesses, academia, and non-government organizations, prioritized needs and practices were identified using SSN, and gap analyses were conducted for comparison to global benchmarks. According to the results, the top needs were mainly focused on improving government efficiency and implementation, maintaining healthy indoor environments and obtaining adequate funds; priority practices were mainly focused on governmental action, renewable energy development and pollutant source reduction. The gap analysis indicated that the government efficiency and performance had the largest gap to the benchmark. By using a simple interactive tool to bring different stakeholders into policy making process, this study produces all-around information for decision makers. The results imply that the sustainability of the building industry in China has a much better expectation than governmental performance. (C) 2013 Elsevier Ltd. All rights reserved.